Detection of seismic ULF geo-electrical potential variations as tremor precursors prior to quarry blasts (2009)
A seismic ultra low frequency geo-electrical signal recording instrument was set up in three different quarry sites in the south-western part of Nigeria. This research was embarked upon to detect geo- seismic electrical signals produced from the brittle upper crust during rock loading and fracture as a simulated earthquake precursor. The seismic electromagnetic signals emitting from the interior earth in analogical pattern and detected at the earth surface through the signal detectors were transmitted to a conditioning circuit which not only protected the recording instruments from transients caused by ionospheric disturbances but also attenuated the 50 or 60 Hertz frequency caused by high voltage power transmission lines. The spectral analysis of the ULF signals with sampling of 48 KHz recorded during rock loading and fracture in each of the stations revealed that the amplitudes of the signals decrease with increasing frequency. The geo-electrical potential signals associated with ULF waves were varying during deformation stages of crustal layers of rocks. These signals were recorded a few seconds before and after fracture of the rocks as systematic precursors to the main tremors observed in each of the stations and felt five (5) kilometers away.